2020
DOI: 10.1177/1071100720970189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lateral Column Lengthening on Subtalar Motion in a Cadaveric Model

Abstract: Background: Although lengthening of the lateral column through a calcaneal neck osteotomy is an integral component of flatfoot reconstruction in younger patients with flexible planovalgus deformities, concern exists as to the effect of this intra-articular osteotomy on subtalar motion. The purpose of this study was to quantify the alterations in subtalar motion following lateral column lengthening (LCL). Methods: The subtalar motion of 14 fresh-frozen cadaveric feet was assessed using a 3-dimensional motion ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Subtalar eversion motion was most strongly related to the lateralization of plantar pressure during stance. The question of whether LCL affects the subtalar joint motion has been a subject of debate, as reductions in the subtalar range of motion compared with controls were demonstrated in 1 study while another study showed no differences after a 12-mm LCL procedure 15,16 . In the present study, subtalar eversion motion was strongly influenced by increasing wedge size.…”
Section: Discussionmentioning
confidence: 99%
“…Subtalar eversion motion was most strongly related to the lateralization of plantar pressure during stance. The question of whether LCL affects the subtalar joint motion has been a subject of debate, as reductions in the subtalar range of motion compared with controls were demonstrated in 1 study while another study showed no differences after a 12-mm LCL procedure 15,16 . In the present study, subtalar eversion motion was strongly influenced by increasing wedge size.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that no significant changes in subtalar motion were observed following LCL in the biomechanical cadaveric study. 18 On the other hand, clinical studies showed mixed results. 5,26 No matter how intra-articular invasion affects the subtalar motion, we preserve the integrity of the subtalar joint to reduce the effect on subtalar motion, which is evaluated as insignificant change in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional biomechanical studies are mostly carried out using cadaver models, making it difficult to acquire the strain data of soft tissues and contact characteristics [8]. In this regard, computer simulation based on finite element (FE) analysis is able to obtain internal biomechanical information such as soft tissue strain and joint contact characteristics under predetermined conditions and controlled environment.…”
Section: Introductionmentioning
confidence: 99%